2009
DOI: 10.1172/jci36010
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-anchored uPAR regulates the proliferation, marrow pool size, engraftment, and mobilization of mouse hematopoietic stem/progenitor cells

Abstract: The mechanisms of BM hematopoietic stem/progenitor cell (HSPC) adhesion, engraftment, and mobilization remain incompletely identified. Here, using WT and transgenic mice, we have shown that membrane-anchored plasminogen activator, urokinase receptor ( M uPAR) marks a subset of HSPCs and promotes the preservation of the size of this pool of cells in the BM. Loss or inhibition of M uPAR increased HSPC proliferation and impaired their homing, engraftment, and adhesion to the BM microenvironment. During mobilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 60 publications
2
67
0
Order By: Relevance
“…Interestingly, previous studies have shown that uPAR expression is induced by hypoxia in cultured hematological cells (19). Furthermore, using uPARdeficient mice, Tjwa et al reported that membrane-anchored uPAR regulates HSPC adhesion and BM engraftment (17), and we have shown that sLR11 binds to and co-localizes with uPAR on the cell surface of SMCs (41). On the basis of these findings, we now demonstrate that the hypoxia-induced increase in LR11 was accompanied by an elevated level of uPAR, which FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, previous studies have shown that uPAR expression is induced by hypoxia in cultured hematological cells (19). Furthermore, using uPARdeficient mice, Tjwa et al reported that membrane-anchored uPAR regulates HSPC adhesion and BM engraftment (17), and we have shown that sLR11 binds to and co-localizes with uPAR on the cell surface of SMCs (41). On the basis of these findings, we now demonstrate that the hypoxia-induced increase in LR11 was accompanied by an elevated level of uPAR, which FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Many proteins including Sca-1, c-Kit, CD34, and urokinase-type plasminogen activator receptor (uPAR; CD87) have been identified as regulators of HSPC adhesion to osteoblastic niches (12)(13)(14)(15)(16)(17). In fact, recent studies using overexpressing or knock-out mice and cells for angiopoietin-1, thrombopoietin, bone morphogenetic protein-4, Secreted frizzled related protein-1 (Sfrp-1), or uPAR have shown that changes in expression of the respective gene cause disturbed maintenance of normal HSPC pool size and lead to pathological conditions typical of hematological proliferative disease or severe anemia (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of active proteases, including neutrophil elastase, cathepsin G, matrix metalloproteinase (MMP)-9, MMP14, and plasmin, are increased in the bone marrow following G-CSF or chemotherapy administration, largely secondary to the dramatic increase in maturing myeloid cells [43][44][45]. Furthermore, endogenous protease inhibitors, such as serpin A1 and serpin A3, are significantly reduced in the bone marrow following G-CSF administration [46] resulting in a highly proteolytic environment.…”
Section: Proteasesmentioning
confidence: 99%
“…86 A subset of HSPCs expresses uPAR on their surface, which helps tether them to the niche via interactions with VLA-4. 87 On G-CSF treatment, uPAR is cleaved from the cell surface by plasmin 87 and released into the extracellular space, wherein it is subsequently proteolytically cleaved into smaller fragments. 88 Selleri et al 89 suggest that…”
Section: Regulation Of Hspc Mobilization By Uparmentioning
confidence: 99%